Optimal number of implants for complete-arch implant-supported prostheses with a follow-up of at least 5 years: A systematic review and meta-analysis - de Luna Gomes, Jéssica Marcela [UNESP]; Lemos, Cleidiel Aparecido Araújo [UNESP]; Santiago Junior, Joel Ferreira; de Moraes, Sandra Lúcia Dantas; Goiato, Marcelo Coelho [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2019)
Statement of problem: Consensus is lacking regarding the optimal number of implants for supporting complete-arch prostheses with good survival rates and lower prosthetic complications and marginal bone loss. Purpose: The purpose of this systematic review was to evaluate the influence of the number of implants used for complete-arch prostheses with at least 5 years of follow-up. Material and methods: A search was performed in the PubMed/MEDLINE, Scopus, and Cochrane Library databases according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria and was registered in The International Prospective Register of Systematic Reviews (CRD42016048468). The following was the population, intervention, comparison, outcome (PICO) question: Does the number of implants influence the longevity of complete-arch prostheses? Results: Nineteen studies including 1006 patients with a mean age of 61.44 years were selected for evaluation. The number of implants per jaw ranged between 2 and 9 in the maxilla, mandible, or both jaws. For implant survival rate in complete-arch prostheses with fewer than 5 implants per jaw, the pooled weighted event rate was 1.4% (I 2 =25.26%; P=.211) and 4.2% (I 2 =81.35%; P<.001) for complete arches with more than 4 implants per jaw. For the prosthesis survival rate, the pooled weighted event rate for a complete-arch with fewer than 5 implants per jaw was 1.5% (I 2 =0%; P=.677) and 9% (I 2 =17.33%; P=.304) for complete arches with more than 4 implants per jaw. For prosthesis complications for complete arches with fewer than 5 implants per jaw, the pooled weighted event rate was 19.9% (I 2 =93.5%; P<.001) and 24.5% (I 2 =88.89; P<.001) for complete arches with more than 4 implants per jaw. The mean marginal bone loss for complete arches with fewer than 5 implants per jaw was 1.22 ±0.49 mm (I 2 =99.46; P<.001) and 1.46 ±0.46 mm (I 2 =99.6; P <.001) for more than 4 implants per jaw. Conclusions: The current systematic review indicated no relationship of the number of implants used to support a complete-arch prosthesis with implant survival rate, prosthesis survival rate, prosthesis complications, or marginal bone loss in studies with follow-up periods of between 5 and 15 years.